Jamal Kemal Creative Colorful Work (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
It is known that there is not a single poet who would not write about his Homeland.  But Jamal Kemal's writings on this topic consist of passionate thoughts, feelings and experiences. They have burning feelings of love for the Homeland in which they were born and grew up. The poet's allusions are unique. Several poems on this topic confirm our reasoning. In this regard, the poem " Eng buyuk tuproq " draws attention to itself